Pengaruh Pemberian Fly Ash dan Biochar Sekam Padi terhadap Ketersediaan N, P, K dan Pertumbuhan Terung Ungu (Solanum melongena L.) pada Tanah Alluvial - Manalu, Anggita Yosia; Indrawati, Urai Suci Yulies Vitri; Nuriman, Muhammad (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2026)
Alluvial soils in West Kalimantan have low levels of macronutrients, particularly phosphorus (P) and potassium (K), which hinder the growth of purple eggplant. To improve the chemical properties of these soils, fly ash and rice husk biochar were used as soil amendments, with the aim of increasing soil pH, organic carbon, total nitrogen, available phosphorus, and soluble potassium, as well as promoting plant growth. The study aimed to determine the role and optimal application rates of fly ash and rice husk biochar on the availability of N, P, and K nutrients and the growth of purple eggplant in alluvial soil. The study was designed using a factorial Complete Randomized Design (CRD) with 9 treatment combinations and 3 replications, consisting of Fly Ash (0, 1000, 1500 g/polybag) and rice husk biochar (0, 525, 1000 g/polybag). Analysis of variance results showed that fly ash had a significant effect on soil pH and available phosphorus, which played a role in reducing soil acidity and increasing phosphorus availability in alluvial soil. Fly ash did not have a significant effect on organic carbon, total nitrogen, soluble potassium, and plant height. Result show biochar also had no significant effect on any of the soil chemical parameters or plant height, and there was no interaction between the two soil amendments. The A1B2 treatment combination (0 g of fly ash per polybag and 525 g of biochar per polybag) was the optimal treatment, showing the greatest improvement in soil chemical parameters and plant height, indicating that biochar at a moderate dose is more effective at improving soil chemical properties and supporting the growth of purple eggplant under conditions without fly ash.